Reply to Mazzarini et al. comment on 'Unveiling ductile deformation during fast exhumation of a granitic pluton in a transfer zone'. (February 2022) - Spiess, Richard; Langone, Antonio; Caggianelli, Alfredo; Stuart, Finlay M.; Zucchi, Martina; Bianco, Caterina; Brogi, Andrea; Liotta, Domenico
Abstract: In our reply we demonstrate the inconsistency of the comment we received from Mazzarini et al. Our data, models and conclusions are solid and framed in the regional evolution of the Northern Apennines, typified by eastward migration of coeval extensional tectonics and magmatism since late Miocene. We show that understanding the natural processes recognizable in the Elba Island requires a scientific approach based on reproducible, reliable and high-quality datasets, independently of the scale of observation.